Pengetahuan, Sikap, dan Perilaku Perundungan pada Siswa Sekolah Dasar di Wilayah Kecamatan Purwokerto Timur - Rubai, Windri Lesmana; Gamelia, Elviera; Maqfiroch, Arrum Firda Ayu (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Background: Bullying is a problem that is currently increasingly rampant in the education sector, so it requires serious handling. Two out of three children and adolescents in Indonesia have experienced violence throughout their lives. A school environment dominated by violence will harm students, such as feelings of isolation and depression and weakening learning motivation. Aim: This study aims to identify the level of knowledge and attitudes of students and bullying behavior in Elementary Schools. Method: This study uses a cross-sectional approach with a cluster sampling technique. The research location is in six public elementary schools from six sub-districts in the Purwokerto Timur District with a sample size of 211 students. Data collection was conducted in July - August 2024 with univariate and bivariate analysis. Result: The majority of students have good knowledge about bullying (79.5%), and good attitudes about bullying (61.9%). As many as 47.2% of students have been bullied at school, and 52.8% of students admitted to having been victims of bullying by their friends. The majority of bullies are male (54%), and the majority of victims of bullying are female (68%). This study had no significant relationship between knowledge and attitudes towards bullying behavior. Promotive and preventive efforts in schools must be continuously intensified to create a safe learning environment and prevent bullying among students.